HUBUNGAN ANTARA KEPRIBADIAN TANGGUH DAN RELIGIUSITAS DENGAN KESEJAHTERAAN PSIKOLOGIS PADA KORBAN BENCANA ALAM DI YOGYAKARTA - Mabruri, Mohammad Iqbal (Jurusan Psikologi, Fakultas Ilmu Pendidikan, Universitas Negeri Semarang, 2009)
The purpose of this study is to know the correlation between hardiness and religious with psychological well-being of the survivor of natural disaster at DIY. There are hypothesis of this study : 1- there are positive correlation between hardiness and religious with psychological well being of the survivor of natural disaster at DIY. 2- the are positive correlation between hardiness and psychological well-being of survivor of natural disaster at DIY. 3- there are positive ceorrelation between religious with psychological well-being of survivor of natural disaster at DIY. The subject of the research were 108 persons whom are being in Segoroyoso village, Pleret of Bantul. The survivor of natural disaster in Bantul include male an female, whom are about 25-65 years old and were Moslem. Every subject was given three scales ; the hardiness scale, religious scale, and psychological well being scale. This study use quantitative methode and regression analysis was used as a statistical data. The result show that : 1-there is a correlation and highly significant between harviness anv religious with psychological well-being of the survivor of natural disaster at Diy (r= 0,308 and p<0,001) and hardiness and religious contributes 9,5%. 2-there is a positive correlation and higly signifant between hardiness with psychological well-being (r=3,307 and p<0,01). 3-there is no correlation between religious with psychological well-being of survivor of natural disaster at DIY (r=0,09 and p<0,01). It turns out that the quantitative data analyzing enriched of this research. Trough the various description, it could be valuable contribution for the study of psychological well being of the survivor of natural disaster at DIY.Â